‘Anyone can teach PR’: From competency to capability - Wolf, Katharina; Sison, M. (2019)
Recruiting for teaching positions in public relations often highlights the issues of academic legitimacy experienced by the educators in the field. Other scholars have examined the issues of academic legitimacy and encroachment by other fields such as marketing and management (Fitch, 2014a; Fitch 2014b; Hatherell & Bartlett, 2006; Hutton, 2010; McKie & Willis, 2012). While public relations scholarship has expanded over the past three to four decades, questions of public relations’ academic legitimacy still continue to be raised.